2016
DOI: 10.1371/journal.pone.0167179
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Electrophysiological Biomarker of Duplication 15q11.2-q13.1 Syndrome

Abstract: BackgroundDuplications of 15q11.2-q13.1 (Dup15q syndrome) are highly penetrant for autism spectrum disorder (ASD). A distinct electrophysiological (EEG) pattern characterized by excessive activity in the beta band has been noted in clinical reports. We asked whether EEG power in the beta band, as well as in other frequency bands, distinguished children with Dup15q syndrome from those with non-syndromic ASD and then examined the clinical correlates of this electrophysiological biomarker in Dup15q syndrome.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
64
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 43 publications
10
64
1
1
Order By: Relevance
“…19-year-olds with a copy number of variants of ASD as Dup15q syndrome have shown excessive beta activity during resting state EEG (Frohlich et al, 2016;Kozhushko, 2018). These findings are consistent with the present pilot study where we identified increased beta power in the spectral features of the EEG.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…19-year-olds with a copy number of variants of ASD as Dup15q syndrome have shown excessive beta activity during resting state EEG (Frohlich et al, 2016;Kozhushko, 2018). These findings are consistent with the present pilot study where we identified increased beta power in the spectral features of the EEG.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, altered beta activity has been reported in REM sleep (Daoust et al, ) and reported for EEG recorded during resting wakefulness in ASD (Kozhushko, ; Wang et al, ) and Dup15q syndrome (a genetic variation that is associated with ASD; Frohlich et al, ). Research with 4‐ to 9‐year‐olds with ASD (Kozhushko, ) and research with 2.5‐ to 19‐year‐olds with a copy number of variants of ASD as Dup15q syndrome have shown excessive beta activity during resting state EEG (Frohlich et al, ; Kozhushko, ). These findings are consistent with the present pilot study where we identified increased beta power in the spectral features of the EEG.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous mathematical work (Pulizzi et al 2016) suggests that the interplay between excitation and inhibition might be responsible for these oscillations. An altered balance between excitation and inhibition could therefore have manifested itself in the oscillations, which are interestingly reminiscent of an in vivo (EEG) biomarker of another autism spectrum disorder syndrome with aberrant GABA A activity (Frohlich et al 2016). However, an alternative hypothesis for this oscillatory activity may come from the known dysregulation of short-term synaptic plasticity in Fragile X (Testa-Silva et al 2012).…”
Section: Discussionmentioning
confidence: 99%